An investigation of query-by-drawing image search on mobile devices - Zhang, Min (2016)
The rapid growth of touchscreen mobile devices has opened up many new opportunities for exploring Content-based Image Retrieval (CBIR) techniques, e.g., it has enabled the development of intuitive and natural user interfaces to facilitate the Query-by-Drawing (QbD) image search paradigm. Although ubiquitous mobile computing holds the promise of drastically changing the ways users search for images from large image repositories, there is yet no comprehensive and systematic study that examines the factors that influence the usability, user behaviours and task performance of a QbD image search mobile application (App). No guidelines and principles exist for designing fundamental user interface components such as the colour picker and little is known how its different designs affect system usability and task performance. Little research exists that examines how different user interface designs affect the ways users draw the queries and how users go about the search process for different types of tasks. The questions of whether or not it is possible or how well users can perform QbD image search by drawing from memory of previously-seen images are unexplored. An understanding of these questions is very important and useful in the development of effective and user-friendly systems for a QbD image search App on touchscreen mobile devices.